Shareholder primacy, controlling shareholders and Malaysia’s Companies Act 2016 - Mohd. Sulaiman, Aiman @ Nariman; Rachagan, Shanty (Taylor and Francis Ltd., 2017)
The predominant corporate governance model within the Commonwealth mimics that of the UK where powers of management are reserved for the board. This director primacy model, however, is being challenged by proposals to expand shareholders’ decision-making rights including giving shareholders the power to initiate their own proposals and to instruct the board. Amidst this debate, Malaysia has passed its new Companies Act 2016 which contains, amongst others, s 195 which empowers shareholders to make binding recommendations to the board relating to the management of the company. Empowering shareholders by giving them such powers have been the subject of intense criticisms. This article examines s 195 and the shareholders participation eco-system to provide an idea of the law in practice as well as to address the concerns relating to giving shareholders such expansive power. This article advances the view that the decision-making framework under the Companies Act 2016 and the actual functioning of the power to instruct show that these criticisms may be unfounded and the potential setbacks of shareholder empowerment can be minimised through judicious use of legal rules.